Percentage of mangrove canopy coverage and community structure in Batanta Island and Salawati Island, Raja Ampat District, West Papua Province - Schaduw, Joshian N.W. (Universitas Sam Ratulangi, 2020)
The research aimed at monitoring the condition of mangrove communities in Batanta Island and Salawati Island, Raja Ampat District, West Papua Province. It used method developed by the Indonesian Institute of Sciences Research Center for Oceanography (P2O LIPI). Method in determining the percentage for the coverage of mangrove communities used a hemispherical photography and the data analysis used ImageJ software in excel tabulation. The result showed that mangrove canopy coverage has decreased from 85.73% in 2017 to 84.14% in 2018. Since the observations in 2015, the percentage of mangroves had no significant change. In average the percentage increased as much as 3.45% from 75.09% in 2015 to 78.54% in 2016. Moreover, it increased again by 7.20% in 2017 (85.73%). It indicates that the average change percentage of mangroves is not significant, and it can be concluded that the mangrove ecosystem in this area does not degrade significantly and has a good growth rate. The average density value was 1254.3 trees per hectare in the period of 2016-2018 or it increased to about 16.5% since 2015. The number of species found at the observation site were 5 species (Rhizophora mucronata, Rhizophora apiculata, Bruguiera gymnorrhiza, Sonneratia alba, and Xylocarpus granatum) scattered in eight observation stations. From these results it can be concluded that mangrove condition at the research location is stable and gets support for the survival of biota associated therein.